Cyperaceous in Rio Grande do Sul - Bertls, Andrej (Pesquisa Agropecuaria Brasileira, 2024)
The present work results from continuous studies on cyperaceous in Rio Grande do Sul. In this work, only those species found and studied by the deceased Priest Balduíno Rambo and the author are mentioned. The species are recorded and filed in accordance with the system proposed by Dr. M. Barros (Argentina) with indications given for the ecological position for each species.